Optimal Contracts with Performance Manipulation - BEYER, ANNE; GUTTMAN, ILAN; MARINOVIC, IVÁN (Journal of Accounting Research, 2014)
ABSTRACT We study optimal compensation contracts that (1) are designed to address a joint moral hazard and adverse selection problem and that (2) are based on performance measures, which may be manipulated by the agent at a cost. In the model, a manager is privately informed about his productivity prior to being hired by a firm. In order to incentivize the manager to exert productive effort, the firm designs a compensation contract that is based on reported earnings, which can be manipulated by the manager. Our model predicts that (1) the optimal compensation contract is convex in reported earnings; (2) the optimal contract is less sensitive to reported earnings than it would be absent the manager's ability to manipulate earnings; and (3) higher costs of manipulating reported earnings (e.g., due to higher governance quality) are associated with higher firm value, lower expected level of earnings management, and higher output.